Towards a psychological framework on time perception in patients with chronic tinnitus - Dauman, Nicolas (Frontiers in Aging Neuroscience, 2023)
Although disabling tinnitus is a chronic auditory phantom sensation, current knowledge on time perception (i.e. subjective time) in sufferers is limited and unsystematic. This theoretical analysis provides a first approach to this topic, highlighting the heterogeneity of time perception in humans as shown in various research areas.. This heterogeneity is inherently related to goal attainment. Our immediate perception of time is restricted to present moment and recent past, whereas our sense of time is mostly future-oriented and represented as our past in a mental time line. The heterogeneity of time translates into a tension between anticipated changes one wants to see happen and full commitment that is required to goal attainment. Tinnitus sufferers are intensely aware of this tension in their self-perception. Their most compelling desire is that they no longer perceive tinnitus, but they get closer to this goal only by avoiding to put all their thoughts into it. Our analysis provides new perspectives on acceptance of tinnitus in relation to this time paradox. Building on the Tolerance model and the role of self-awareness in time perception, we contend that the main way for patients to gain long-term self-confidence is to engage in the present moment. Attention to this attitude is obscured in chronic sufferers by worries and ruminations associated with the ongoing presence of tinnitus. We provide arguments that time perception is a social perception, emphasizing the role of rewarding interactions in helping sufferers to overcome the feeling of being prevented from living in the moment. In the course of improvement towards acceptance, different changes in time perception are hypothesized that promote individuals’ disengagement from unattainable goal (i.e. tinnitus suppression). A framework for future research is proposed, which distinguishes individuals’ behaviors and associated emotions in relation to the time paradox.